2010
DOI: 10.1002/ctpp.201010010
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity in Warm Dense Plasmas Beyond the Average‐Atom Model

Abstract: The exploration of atomic properties of strongly coupled partially degenerate plasmas, also referred to as warm dense matter, is important in astrophysics, since this thermodynamic regime is encountered for instance in Jovian planets' interior. One of the most important issues is the need for accurate equations of state and transport coefficients. The Ziman formula has been widely used for the computation of the static (DC) electrical resistivity. Usually, the calculations are based on the continuum wavefuncti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The average atom potential leads to surprisingly poor agreement in magnitude for many cases. This is surprising because it has been used frequently in the past [19,23,24], and because it is consistent with Evans' [30] original formulation. The failing may be due to the muffin-tin approximation.…”
Section: A Discussion Of the Comparison To Qmdmentioning
confidence: 94%
See 2 more Smart Citations
“…The average atom potential leads to surprisingly poor agreement in magnitude for many cases. This is surprising because it has been used frequently in the past [19,23,24], and because it is consistent with Evans' [30] original formulation. The failing may be due to the muffin-tin approximation.…”
Section: A Discussion Of the Comparison To Qmdmentioning
confidence: 94%
“…The screened potential (25) and the average atom potential (26) have been widely used with the Ziman-Evans formula to calculate conductivities [13,23,24,40,41]. A third type of potential, that of a single pseudo-atom, has also been used [1,13].…”
Section: Scrmentioning
confidence: 99%
See 1 more Smart Citation
“…One cause of the predicted minimum in the electrical conductivity is the onset of spatial ordering in the ions; the plasma begins to take on characteristics of a liquid metal. In liquid metals, the standard theory of conduction is based on the Ziman formula, which has been applied to warm and hot dense plasmas by many authors [62][63][64][65][66]. In particular, Burrill et al demonstrated that the electrical conductivity minimum can only be captured by a Ziman-type theory when ionic correlations are accounted for.…”
Section: A the Conductivity Minimummentioning
confidence: 99%
“…Average atom models have been used successfully for many years for equation of state calculations [8][9][10][11][12][13]. They have also been used for electrical conductivity calculations, primarily by coupling to the Ziman-Evans (ZE) formula [14][15][16][17][18][19][20]. Recently, a systemic comparison of calculations of electrical conductivity using this method against Kubo-Greenwood KS-DFT-MD calculations [14] showed generally very good agreement between the methods provided that a judicious choice was made when coupling the average atom model to the ZE formula.…”
Section: Introductionmentioning
confidence: 99%